2000
DOI: 10.1212/wnl.54.8.1681
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of pathologically proved cholesterol emboli to the brain

Abstract: Cholesterol emboli (CE) to the brain are an important but often unrecognized cause of stroke. The authors reviewed 29 cases of brain CE identified on autopsy. Most patients were elderly (mean age, 74 years) and presented with encephalopathy and acute renal failure. Ten patients developed symptoms spontaneously, 19 after a procedure involving manipulation of the aorta. Brain imaging revealed multiple, small ischemic lesions and border zone infarcts in 11 of 17 patients. Pathology in most patients demonstrated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 8 publications
3
24
1
4
Order By: Relevance
“…Interestingly, our DWI lesion pattern analysis showed that most of the lesions with vulnerable AAA were small and located in cortical and border-zone regions. Our DWI results are in line with the previous autopsy study investigating cholesterol emboli that can be derived from vulnerable AAA [31]. …”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, our DWI lesion pattern analysis showed that most of the lesions with vulnerable AAA were small and located in cortical and border-zone regions. Our DWI results are in line with the previous autopsy study investigating cholesterol emboli that can be derived from vulnerable AAA [31]. …”
Section: Discussionsupporting
confidence: 90%
“…Individuals with a higher atherosclerotic burden in the aorta have higher rates of systemic embolization, either spontaneously or from catheter manipulation (26 -28). In an autopsy series of 29 patients who had cholesterol emboli to the brain, 55% also had emboli to their kidneys (29). The majority of the patients in this series underwent procedures involving manipulation of the aorta, and 10% of patients died due to complications of acute renal failure.…”
Section: Discussionmentioning
confidence: 90%
“…55 Brain imaging typically reveals small ischemic lesions and border zone infarcts. 56 Transcranial Doppler (TCD) ultrasonography, which was first described in 1982, can be used to detect microemboli in the cerebral circulation. 57 Microemboli are detected as highintensity transient signals superimposed on standard spectral Doppler flow velocity tracings of red blood cells in cerebral arteries.…”
Section: Central Nervous Systemmentioning
confidence: 99%